Fructose-Derived Carbon Dots as Selective Antitumor Agents in Breast Cancer Therapy: Synthesis, Characterization, and Biological Evaluation - Sofia Magalhães; Carla Luís; Abel Duarte (J)
This study explored a novel method using fructose-derived carbon dots (FCDs) for antitumor therapy in breast cancer (BC), marking a pioneering use of fructose as a carbon source for nanoparticle synthesis. BC, known for its complexity and heterogeneity, was chosen as a model due to its increasing mortality and incidence rates. The FCD synthesis involved the decomposition of fructose through microwave irradiation, followed by purification and characterization using techniques such as transmission electron microscopy, dynamic light scattering, fluorescence spectrophotometry, and Fourier-transform infrared spectroscopy. The FCDs, ranging in size from 2 to 6 nm, presented a hydrodynamic diameter below 2 nm, a spherical morphology, and a crystalline structure. As expected, FCDs were composed by carbon, oxygen, and hydrogen, and exhibited fluorescence with absorption and emission spectra at 405 nm and around 520 nm, respectively. Cell-based assays on breast epithelial and tumor cell lines demonstrated a dose-dependent response, with a decreased viability rate more pronounced in breast tumor cells. In conclusion, FCDs showed significant potential as selective antitumor agents for breast cancer therapy. The comprehensive characterization and cell-based assay evaluations provided valuable insights into the applications of these nanoparticles in breast cancer treatment, highlighting their selective toxicity and impact on tumor cells.